Action towards hope: Addressing learner behaviour in a classroom - LeeFon, Raelene (Koers, 2013)
Unruly learners and disciplinary problems are an intractable part of every teacher’s teaching experience. It appears that, even though most schools have enacted a code of conduct to regulate learner behaviour, this does not always have the desired effect. Disciplinary problems in schools impact negatively on the teaching and learning environment as well as on teachers’ personal and professional well-being and morale. Framed within the context of a biblical worldview, this article narrates the experiences of one teacher who decided to take action towards hope. The situation in her classroom was quite desperate with learners coming to school unprepared and behaving very badly and parents being uninterested in the performance of their children at school. She realised that she could not change the learners or their parents unless she started with herself. In this context, she, as a postgraduate student under the supervision of the co-authors, embarked on an action-research project to promote positive learner behaviour. By collaborating with the learners on a set of classroom rules, engaging in reflective teaching and changing her own behaviour towards the learners, the situation in her classroom improved. Based on her experiences, this article argues that teachers should empower themselves with knowledge and a better understanding of the concept of discipline rather than viewing the classroom as a battlefield. It is important to acknowledge and show respect and appreciation for each learner in his or her own context.